Edukasi Pemanfaatan Pelayanan Posyandu di Kelurahan Legok - Fithriyani Fithriyani; Rino M; Mila Triana Sari (Jurnal Abdimas Kesehatan (JAK), 2023)
Posyandu is one form of Community Resource Health Effort (UKBM) which is managed and organized from, by, for and with the community in the implementation of health development, in order to empower the community and provide convenience to the community in obtaining basic health services to accelerate the reduction in maternal and infant mortality rates. The lack of public awareness about health problems tends to ignore health problems and does not utilize health services, especially posyandu. Therefore, in supporting the improvement of knowledge and public welfare, health workers play a role in assessing problems that occur and planning health problems through health promotion programs. The people of Legok Village have less awareness and willingness in improving the degree of health and utilization of health services, especially posyandu. The purpose of this community service activity is to increase public understanding of the use of posyandu services in Legok Village. The method of activities carried out in the form of health promotion carried out to solve these problems is by educating about the use of posyandu services. The place of implementation was carried out at the RT 08 house in Legok Village, Jambi City on July 29, 2022, the implementation of community service activities was carried out from March to August 2022 with team members and professional students. There were 11 participants present. The results of the evaluation showed an increase in participants' knowledge by an average of 90%. Community participation needs to be increased in the posyandu program, it is necessary to provide correct and targeted information.